Successful delivery of spontaneously conceived twins in a single horn of a bicornuate uterus: A case report - Katherine Adams; Lee Minuzzo (Elsevier, 2019)
Uterine malformations are associated with infertility, recurrent miscarriage and preterm birth, to variable degrees. Accurate classification is crucial to management. A 30-year-old primigravida presented with spontaneous conception of monochorionic diamniotic twins in the right horn of a bicornuate uterus, previously diagnosed as a didelphys uterus. At 28 + 5 weeks of gestation, the patient had preterm prelabour rupture of membranes followed by preterm labour, resulting in the patient undergoing an emergency caesarean section, with the successful delivery of live twin males. Keywords: Monochorionic, Diamniotic, Didelphys, Uterine malformation